2015
DOI: 10.1155/2016/8214631
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lycopene Preexposure on UV‐B‐Irradiated Human Keratinocytes

Abstract: Lycopene has been reported as the antioxidant most quickly depleted in skin upon UV irradiation, and thus it might play a protective role. Our goal was to investigate the effects of preexposure to lycopene on UV-B-irradiated skin cells. Cells were exposed for 24 h to 10 M lycopene, and subsequently irradiated and left to recover for another 24 h period. Thereafter, several parameters were analyzed by FCM and RT-PCR: genotoxicity/clastogenicity by assessing the cell cycle distribution; apoptosis by performing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 81 publications
1
35
0
Order By: Relevance
“…Similar to the findings presented here, extensive studies have also reported the anti-proliferative and/or pro-apoptotic effects of lycopene in the development of skin cancer after UVB exposure [Fazekas et al, 2003;Stahl and Sies, 2007;Reuter et al, 2010;Ascenso et al, 2016]. However, there are also some other studies report a negative effect of lycopene on skin photocarcinogenesis context [Yeh et al, 2005;Burgess et al, 2008].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to the findings presented here, extensive studies have also reported the anti-proliferative and/or pro-apoptotic effects of lycopene in the development of skin cancer after UVB exposure [Fazekas et al, 2003;Stahl and Sies, 2007;Reuter et al, 2010;Ascenso et al, 2016]. However, there are also some other studies report a negative effect of lycopene on skin photocarcinogenesis context [Yeh et al, 2005;Burgess et al, 2008].…”
Section: Discussionsupporting
confidence: 86%
“…Normal human epidermal keratinocytes (NHEK) cells were purchased from Invitrogen and cultured in EpiLife medium (Invitrogen Co., Shanghai). Cells were pretreated with lycopene (10 mmol) at 37°C for 24 h, and after UV-B irradiation, irradiated cells were incubated under standard culture conditions for a final 24 h period [Stahl and Sies, 1996;Hwang and Lee, 2006;Ascenso et al, 2016]. The UVB and drug treatment experiments were started when cells had reached 70-80% confluence.…”
Section: Cell Culture Uvb Irradiation and Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin cancer can result from exposure to ultraviolet (UV) radiation emitted by the sun and by halogen lamps. Experimental studies of metastatic melanoma are very challenging because systemic treatments are often ineffective and the rapid spread of melanoma cells to retain an intensive property of the cellular spreading which happens later is pathologically confusing [ 5 ]. Although melanoma is not a major cause of tumorous symptoms, melanoma is a major cause of death in patients with skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Melanin scavenges free radicals to inhibit lipid peroxidation and protects the skin from UV damage, but melanin can also be deoxidized by an antioxidant. Therefore, melanin is called the radical sink [ 2 , 16 , 17 ]. A lack of melanin reduces the protection for the skin, so ROS stimulates melanocyte to produce more melanin [ 18 ].…”
Section: Discussionmentioning
confidence: 99%